Thailand's Learning Management Development for 21st Century Students Based on Singapore's Framework - Suparada Prapawong (2020)
© 2019 IEEE. According to the concept of education as a means of behavioral change experienced within relationships and interactions between teachers, students, and the environment, learning management makes for a compelling topic of study. The objectives of this research are to study learning management as well as ways to develop learning management. This study is a qualitative research using document analysis tools. Learning management is a systematic process covering operations from planning, learning management, to evaluation. Teachers must be aware of students' nature and supportive learning environments for students of whom they are in charge. For 21st century students, the educational culture has changed from a receiving culture to a producing culture. Technology has become significant in learning management for 21st century students. The model of Singapore's educational framework 'thinking schools, learning nation', 'teach less, learn more', 'tight, loose, tight', and 'professional learning communities' are remarkable examples to consider applying in Thailand in order to develop learning management systems.